2019
DOI: 10.1039/c9gc01659g
|View full text |Cite
|
Sign up to set email alerts
|

Organic aluminum hydrides catalyze nitrile hydroboration

Abstract: The eco-friendly and highly efficient catalytic hydroboration of nitriles has been elucidated by using organic aluminum hydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 36 publications
3
58
0
Order By: Relevance
“…Among metal catalyzed processes, transition metal and even rare earth metal complexes have been studied (Scheme ). There is also a recent surge in utilization of s ‐ and p ‐block elements and till date, several research groups have studied the hydroboration of carbonyl and to some extent imine compounds using main‐group element (Ca, Mg, Al, Si) based systems (Scheme ). Alkali metal based compounds for example, n BuLi and NaOH have also been utilized for the same process .…”
Section: Methodsmentioning
confidence: 99%
“…Among metal catalyzed processes, transition metal and even rare earth metal complexes have been studied (Scheme ). There is also a recent surge in utilization of s ‐ and p ‐block elements and till date, several research groups have studied the hydroboration of carbonyl and to some extent imine compounds using main‐group element (Ca, Mg, Al, Si) based systems (Scheme ). Alkali metal based compounds for example, n BuLi and NaOH have also been utilized for the same process .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, efficient transition-metal-free dihydroboration of nitriles has been achieved with main group element catalysts based on Li, [40] Davit Hayrapetyan was born and raised in Armenia. Mg, [41,42] B, [43] Al [44][45][46][47][48] and Zn [49] systems. All these reports are discussed below with an emphasis on advantages and limitations of hydroboration methods, experimental conditions, substrate scope and functional group tolerance.…”
Section: Transition Metal Catalysts 21 Early Attempts: Mo-catalyzedmentioning
confidence: 99%
“…[56,57] The majority of main group metal systems developed for hydroboration of nitriles concern aluminum catalysts. [44][45][46][47][48] Thus, the first example of such transformations was reported in 2018 by Cowley and Thomas et al, who employed LiAlH 4 as a precatalyst for a series of hydroborations of alkenes, alkynes and ketones with HBPin. Within the scope of these catalytic trials, the authors also reported hydroboration of 4-trifluoromethylbenzonitrile proceeded with full conversion within 6 h at room temperature using 1 mol% of LiAlH 4 .…”
Section: Main Group Metal Catalystsmentioning
confidence: 99%
See 2 more Smart Citations